A Review on Effect of Smoking During Pregnancy (International Journal of Innovative Research in Engineering & Management, 2023)
The early phases of a child's  neurodevelopment have a major influence on their future  human resources and health. On the other hand, the effects  of prenatal risk factors on child neurodevelopment remain  little known. This study looks at the effects of mother  smoking while pregnant on baby neurodevelopment  between the ages of 3 and 24 months, as well as the links  to socioeconomic status (SES). The information comes  from a one-of-a-kind group of South American teenagers.  Smoking has a major deleterious influence on  neurodevelopment, with the effects being particularly  obvious in those of poor socioeconomic status. The study's  results highlight the need of early interventions that begin  before and continue throughout pregnancy to promote  newborn development and current human capital  attainment. Even when people get the best results, the  majority of people still smoke while they're pregnant, even  though they know that smoking can hurt them and their  unborn child. The act of smoking is associated with severe  stress, such as that caused by a demanding job or child care  responsibilities, according to recent studies. Pregnant  women who smoke do it for a variety of reasons, including  controlling their weight growth or coping with negative  emotions like as loss.
Keywords: Child Development; Child Health; Human Capital; Neurodevelopment; Smoking